Lachenalia festiva (Hyacinthaceae subfam. Hyacinthoideae tribe Massonieae), a new species from South Africa - Martínez-Azorín, Mario; Duncan, Graham D.; Pinter, Michael; Crespo, Manuel B.; Alonso-Vargas, María Ángeles; Villar-García, José Luis (Phytotaxa, 2026)
Our field explorations in South Africa revealed an undescribed species of Lachenalia occurring in a quarter degree square previously unrecorded for the genus, in an arid region of northwestern South Africa between Brandvlei and Williston. The new species shares the diagnostic characters of the genus, including the zygomorphic flowers, but it is readily distinguished by its single leaf ornamented with short appressed, branched trichomes and elongated translucent hairs borne on distinct pustules, hypogeal bulb covered with leathery, blackish outer tunics and extended into a hypogeal neck of 3–4 cm long, and the magenta or purplish speckled or mottled tepals, peduncle and lower portion of the leaf, among other characters. A complete morphological description of the new species as well as data on ecology, distribution, and differences with related species, are provided.